Proteinuria, impaired kidney function, and adverse outcomes in people with coronary disease: analysis of a previously conducted randomised trial. Issue 7555 (19th May 2006) - Tonelli, Marcello; Jose, Powell; Curhan, Gary; Sacks, Frank; Braunwald, Eugene; Pfeffer, Marc
Abstract: Objectives To determine whether data on proteinuria are useful for refining estimates of risk based on kidney function alone, and whether the results of kidney function tests can be a useful adjunct to data on proteinuria. Design Analysis of data from a randomised trial. Impaired kidney function was defined as low glomerular filtration rate (< 60 ml/min/1.73 m 2 ) and proteinuria ( 1+ protein) on dipstick urinalysis. Setting Study of cholesterol and recurrent events: a randomised trial of pravastatin 40 mg daily versus placebo. Participants 4098 men and women with previous myocardial infarction. Main outcome measures All cause mortality and cardiovascular events. Results 371 participants died in nearly 60 months of follow-up. Compared with participants without proteinuria or impaired kidney function, patients with both characteristics were at high risk (hazard ratio 2.39, 95% confidence interval 1.72 to 3.30), and those with only proteinuria or only impaired kidney function were at intermediate risk (1.69, 1.32 to 2.16; 1.41, 1.12 to 1.79, respectively) of dying from any cause. The results were similar for cardiovascular outcomes, including new cases of heart failure, stroke, and coronary death or non-fatal myocardial infarction. A graded increase in the risk of all cause mortality was seen for severity of renal impairment and degree of proteinuria by dipstick. Conclusions The presence or absence of proteinuria on dipstick urinalysis may be used to refine estimates of risk based on kidney function alone.